An Overview of the Status and Challenges of CO2 Storage in Minerals and Geological Formations - Kelemen, Peter; Benson, Sally M.; Pilorgé, Hélène; Psarras, Peter; Wilcox, Jennifer (Frontiers in Climate, 2019)
Since the Industrial Revolution, anthropogenic carbon dioxide (CO2) emissions have grown exponentially, accumulating in the atmosphere and leading to global warming. According to the IPCC (IPCC Special Report 2018), atmospheric warming should be less than 2 ℃ to avoid the most serious consequences associated with climate change. This goal can be achieved in part by reducing CO2 emissions, together with capturing and sequestering CO2 from point sources. The most mature storage technique is sequestration in deep saline aquifers. In addition, CO2 can be mineralized and sequestered in solid form by various techniques: ex-situ, surficial and in situ mineralization. Ex situ and surficial approaches may produce valuable products while mitigating environmental hazards. In-situ mineralization uses ultramafic and mafic geological formations for permanent, solid storage. A portfolio that limits warming to less than 2 ℃ by 2100 will include avoiding CO2 emissions and removal of CO2 from air. Regardless of the specific mix of approaches, it will be essential to permanently sequester tens of billions of tons of CO2. Maximizing the potential of all of these storage technologies will help to meet global climate goals. The research agenda published by the National Academy of Science (NASEM 2019) calls for about $1 billion over a 10-20 year time period to advance deployment of CO2 sequestration in deep sedimentary reservoirs at the GtCO2/yr scale and develop CO2 mineralization at the MtCO2/yr scale. This overview study presents the advantages, drawbacks, cost, and CO2 storage potential of each technique, the current and future projects in this domain, and potential sequestration options in geologic formation around the world.